Strengthening Fraternal Life in Religious Communities through Spirituality Coaching, Faith Communication, and Pastoral Assistance - Sihol Situmorang (Abdimas Paspama, 2023)
Fraternal life is a fundamental element in a religious community, but social change, individualism, the use of digital media, and reduced interpersonal communication can weaken the quality of relationships, joint prayer, solidarity, and service. This Community Service activity aims to strengthen fraternal spirituality, faith communication, reconciliation skills, and pastoral assistance in religious communities. The program uses a pastoral-participatory approach through needs identification, theological seminars, Scripture reflection, Focus Group Discussion, faith sharing, active listening exercises, conflict resolution simulations, and the preparation of community commitments. Evaluation is designed through pre-test and post-test, observation, simulation rubric, written reflection, and periodic monitoring. The results showed an increase in the average score from 53.2 to 84.8 in the aspects of fraternal spirituality, faith communication, reconciliation, solidarity, and ministry participation. Qualitative changes are seen in increased openness of participants, the ability to express opinions without blame, willingness to accept corrections, and a commitment to building a culture of dialogue. These findings show that coaching that integrates theological foundations, community experiences, communication exercises, and ongoing mentoring can strengthen communities as communio. The sustainability of the program is directed through regular reflection meetings, personal mentoring, community evaluation, and development of coaching modules.